Two modes of climatic control in the Holocene stalagmite record from the Japan Sea side of the Japanese islands. (24th August 2015) - Sone, Tomomi; Kano, Akihiro; Kashiwagi, Kenji; Mori, Taiki; Okumura, Tomoyo; Shen, Chuan‐Chou; Hori, Masako
Abstract The Holocene stalagmite FG01 collected at the Fukugaguchi Cave in Itoigawa, central Japan provides a unique high‐resolution record of the East Asian winter monsoon. Because of the climate conditions on the Japan Sea side of the Japanese islands, the volume of precipitation during the winter is strongly reflected in the stalagmite δ18O signal. Examination of the carbon isotopes and the Mg/Ca ratio of FG01 provided additional information on the Holocene climate in Itoigawa, which is characterized by two different modes separated at 6.4 ka. Dripwater composition and the correlation between the δ13C and Mg/Ca data of FG01 indicate the importance of prior calcite precipitation (PCP), a process that selectively eliminated 12C and calcium ions from infiltrating water from CO2 degassing and calcite precipitation. In an earlier period (10.0–6.4 ka), an increase in soil pCO2 associated with warming and wetting climate trends was a critical factor that enhanced PCP, and resulted in an increasing trend in the Mg/Ca and δ13C data and a negative correlation between the δ13C and δ18O profiles. A distinct peak in the δ13C age profile at 6.8 ka could be a response to an increase of approximately 10% in C4 plants in the recharge area. At 6.4 ka, the climate mode changed to another, and correlation between δ18O and δ13C became positive. In addition, a millennial‐scale variation in δ18O and pulsed changes in δ13C and Mg/Ca became distinct. Assuming that δ18O and PCP were controlled by moisture in the later period, the volume of precipitation was high during 6.0–5.2, 4.4–4.0, and 3.0–2.0 ka. In contrast, the driest interval in Itoigawa was during 0.2–0.4 ka, and broadly corresponds to the Little Ice Age.